Thyroid ultrasound volume, structure and function after long-term high exposure of large population to polychlorinated biphenyls, pesticides and dioxin - Langer, Pavel; Tajtáková, Mária; Kočan, Anton; Petrík, Ján; Koška, Juraj; Kšinantová, Lucia; Rádiková, Žofia; Ukropec, Jozef; Imrich, Richard; Hučková, Miloslava; Chovancová, Jana; Drobná, Beáta; et al. (Chemosphere (Oxford), 2007)
We examined 2046 adults (834 males and 1212 females aged 20–75 years) from polluted district in East Slovakia (POLL) and two neighboring upstream and upwind located districts of background pollution (BCGR). By ultrasound we estimated the thyroid volume (ThV), hypoechogenicity (HYE), nodules and cysts. Serum levels of thyrotropin (TSH), thyroperoxidase antibodies (TPOab) and thyroglobulin were estimated by electrochemiluminiscent assay and these of 15 PCB congeners, p, p′-DDE, p, p′-DDT, hexachlorobenzene (HCB) and hexachlorocyclohexane by high-resolution gas chromatography. In 320 subjects also selected hydroxylated and methylsulfonated PCB metabolites, polychlorinated dibenzo-dioxins (PCDDs), -furans (PCDFs), five dioxin-like coplanar and eight mono-ortho PCB congeners were estimated. Urinary iodine was measured by automatic microplate method. Reciprocal positive association was found between three major POPs (PCBs, DDE and HCB), the levels of these and also PCDDs plus PCDFs in polluted area being considerably higher than in background pollution area. ThV in groups of males and females from POLL with high PCBs level was significantly higher ( p < 0.001 by t-test) then in age and sex matched groups from BCGR with low PCBs level. In 1048 males and females aged <60 years with serum PCBs level >1000 ng g −1 lipid (median = 1756 ng g −1) a significant effect of age on ThV was found ( p < 0.01 by ANOVA), while in 921 respective subjects with PCBs level <1000 ng g −1 (median = 661 ng g −1) it was not. These findings supported the view on the additional effect of PCBs on ThV other than that of age. Since the urinary iodine in both districts showed optimal range, any interfering effect of unsatisfactory iodine intake on ThV may be excluded. The frequency of autoimmune thyroiditis signs such as HYE, increased serum level of TPOab and TSH resulting in subclinical or overt thyroid hypofunction was positively associated with sex, age and organochlorine levels. The increase of such frequency in males with POPs levels was much more abrupt than that in females. No considerable differences in the frequency of thyroid nodules as related to PCBs level were found.